2015
DOI: 10.1186/1758-5996-7-s1-a173
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of inpatient diabetes education throughout a structured questionnaire

Abstract: Figure 1 Scores for patients evaluated before and after education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Since their validation studies were not found, the authors were contacted and requested to provide them. Both (16,17) had used unvalidated instruments. In both cases, the instruments were excluded because it was impossible to analyze the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Since their validation studies were not found, the authors were contacted and requested to provide them. Both (16,17) had used unvalidated instruments. In both cases, the instruments were excluded because it was impossible to analyze the studies.…”
Section: Resultsmentioning
confidence: 99%